INTENSI PENGGUNAAN FINANCIAL TECHNOLOGY (FINTECH) SEBAGAI SISTEM PEMBAYARAN BAGI PELAKU UMKM PADA ASOSIASI PEARL NTB - SOFIATI WARDAH; RUSLI AMRUL; NURUL ANISA (Universitas Mahasaraswati K. Mataram, 2023)
Financial technology is the result of a combination of financial services with technology which is ultimately widely used in today's digital era. This study aims to examine the effect of personalization, access ability, technological innovation, and social factors on the intention to use financial technology so that this research variable consists of 4 (four) independent variables, namely personalization (X1), access ability (X2), technological innovation (X3 ) and social factors (X4) and the dependent variable is the intention to use financial technology (Y). The research method uses quantitative associative with the population members of the Association of Traders and Craftsmen Pearl Lombok (PEARL) NTB as many as 120 SMEs. Samples were taken using the saturated sampling method where the entire population is a sample. Data were obtained by distributing questionnaires to all members of the PEARL NTB association. Questionnaires that return and can be used as many as 50 questionnaires. The data were analyzed using Multiple Linear Regression with Statistic Program for Social Science (SPSS) version 20 program. The results of this study indicate that personalization, access capabilities, technological innovation, and social factors partially significantly influence the intention to use financial technology. The results of this study also show that the independent variables (personalization, ability to access, technology innovation, and social factors) can influence the dependent variable (intention to use financial technology) by 92,1%. While the remaining 7,9% is influenced by other variables outside the regression model used in this study.